Assessment of feeding practices and morbidity patterns of infants in a rural field practice area of Punjab: a longitudinal study - Singh, Geetika; Lal, Mohan (International Journal of Research in Medical Sciences, 2020)
Background: Faulty feeding practices and infections have a detrimental effect on an infant’s health. Although, breastfeeding is almost universal in India, rates of early initiation, Exclusive Breast Feeding (EBF) and timely complimentary feeds are far from desirable. This takes a heavy toll on their health and increases their susceptibility to develop several morbidities including Diarrhoea and Respiratory Tract Infections. Thus, this study was undertaken to assess the feeding practices and morbidity patterns of infants and to determine their association. Methods: It was a longitudinal study on a birth cohort of 99 infants in the rural field practice area of GMC, Amritsar who were followed up to 6 months of birth. Baseline data on sociodemographic profile and breast feeding was collected in the first visit. Weaning practices and any morbidity suffered during six months’ period were assessed at the follow up visit. Results: Breast feeding was initiated in majority 88.87% but it was delayed in more than half (54.02%) of infants. Customs like prelacteal feeding (76.8%) and discarding colostrum (50.57%) were quite prevalent. EBF was practiced by most 65.51%. In around a quarter of infants, delayed or faulty weaning was observed. Diarrhea was the commonest morbidity (49.09%) followed by ARI (32.73%). Significant association (p<0.05) was observed between the feeding practices and infant morbidities especially diarrhoea. Conclusions: Mothers should be educated more effectively regarding benefits of early and exclusive breast feeding and correct weaning practices. Emphasis should also be placed on increasing awareness in the community to bring about a significant change in the deleterious customs and traditions.